Implementation of the Child Friendly City Implementation Policy in Pekanbaru City (Special Protection Cluster Case for Children) - Rhumeta, Rhumeta; Nasution, Mimin Sundari (Journal of Education Technology Information Social Sciences and Health, 2024)
The Child Friendly City Policy (KLA) is one of the Indonesian government's efforts to fulfill children's rights and provide protection to children in a city/district with the hope that children can grow and develop well. This research aims to find out how the Child Friendly City Implementation Policy is implemented in Pekanbaru City (Case of the Special Protection Cluster for Children) as well as the inhibiting factors faced in implementing the Child Friendly City (KLA) implementation policy in Pekanbaru City, especially in the special protection cluster for children. This research uses implementation theory by Van Metter and Van Horn in Agustino (2020: 151), namely there are 6 indicators, including: Policy size and objectives, resources, characteristics of implementing agents, attitudes or tendencies of implementers, communication between organizations and implementing activities, as well as the economic, social and political environment. This research uses a type of qualitative research which is descriptive analysis. Using interview, observation and documentation data collection techniques. Based on the results of this research, it can be concluded that the implementation of the Child Friendly City Implementation Policy in Pekanbaru City (Special Protection Cluster Case for Children) can be said to be less effective. It can be seen from the limited resources (financial resources, human resources, and facilities and infrastructure resources), the characteristics of implementing agents who are not yet firm in providing punishment for perpetrators who cause children to become victims, communication between organizations and implementing activities related to socialization is lacking. , as well as the economic, social and political environment related to the economic and social background of the community that will implement special protection for children, where communities with low economic conditions tend to have attitudes that are unwilling to change. And the inhibiting factors are the uneven distribution of information to target groups and the lack of cooperation between parents and the department in providing special protection for children.